Perancangan Aplikasi Sistem Informasi Reservasi Kamar Hotel Berbasis Web pada Shang Ratu Hotel Jambi - Novri Adhiatma (JURNAL AKADEMIKA)
In this period the hospitality business growing so rapidly , This is due to the many emerging bagitu hotels. Ranging from small hotels to five-star. With the situation as it is, the competition becomes more intense in the hospitality world. In this case, a hotel must have a strategy that is superior to other hotels. Shang Ratu Hotel Edinburgh is a new agency established since 2012 and engaged in the field of hospitality services, in this business is not only the provision of rooms for lodging but also meeting rooms, reception, restauran t and others. Shang Ratu Hotel is a 4 star hotel in Jambi province. the current spread of the information used, such as the use of brochures, banners, websites and ads in the newspapers. It is less efficient due to Spread the information is not yet complete because the information provided on the website is not updated. Recording reservation dikamar still done manually by filling out the registration form using paper, so it can not be done online as well as leading to waste time in checking the status of the room because the checks must be done by reading the reservation book room one by one, thus the author wanted to design an application that has the purpose to overcome the problems mentioned above, which is a website that can be used for online room reservation to allow potential visitors to the hotel to make hotel room reservations.